Factors affecting road safety compliance in a low- and middle-income country: An observational study from Lebanon - Samar Al-Hajj; Majed El Hechi; Mohamad Chahrour; Sarah H. Farran; Haytham Kaafarani (Public Library of Science (PLoS), 2022)
Road traffic injury is a major public health problem in Lebanon. This study aims to assess compliance with safety measures including seatbelt and helmet use in adults and children, and the prevalence of distracted driving among road users across Lebanon different governorates. It further aims to investigate predictors of compliance with seatbelt and helmet use. A cross-sectional observational field study was conducted at multiple governorates in Lebanon. Data collected included information on vehicles, road users and passengers. Univariate and multivariable logistic regression analyses were performed to identify trends in compliance with safety measures and distracted driving, and predictors of compliance. A total of 13,790 road users were observed. The rate of seatbelt and helmet use were 37.4% and 38.9%, respectively, among adults. Distracted behavior was present in 23.7% of car drivers and 22.8% of motorcyles adult riders. Compliance with seatbelt use was lower outside the capital city Beirut [OR = 5.236 (4.566-6.004), P <0.001], in males [OR = 1.688 (1.52-1.874), P <0.001], in drivers of taxi/vans [OR = 1.929 (1.71-2.175), P <0.001] or trucks [OR = 3.014 (2.434-3.732), P <0.001], and vehicles of lower price [OR = 3.291 (2.836-3.819), P <0.001]. Children vehicle passengers were 87.9% while motorcycles pillion riders were 12.1%. The rates for child car restraint and helmet use were 25.8% and 20.1%, respectively. Predictors of failure to use a child restraint system in vehicles were the youngest age group (0-5 years) [OR = 2.06, CI (1.40-3.02), P<0.001], sitting in the back seat [OR = 1.56, CI (1.09-2.23), P<0.001], ridding in the afternoon [OR = 1.43, CI (1.05-1.94), P = 0.02], and being outside Beirut [OR = 2.12, CI (1.41-3.17), P<0.00]. Public awareness efforts and better enforcement of road safety legislations are needed to increase the alarmingly low rates of compliance with safety measures and safeguard lives on the road.